2022
DOI: 10.1158/1940-6207.capr-21-0581
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Findings in FIT+ and mt-sDNA+ Patients versus in Colonoscopy-only Patients: New Hampshire Colonoscopy Registry Data

Abstract: Few studies compare fecal immunochemical test (FIT) and multi-target stool DNA (mt-sDNA) outcomes in practice. We compared colonoscopy yield following FIT+ or mt-sDNA+ tests to colonoscopies without preceding stool tests in the comprehensive population-based New Hampshire Colonoscopy Registry (NHCR). Outcomes were any neoplasia and an ordered outcome: adenocarcinoma, advanced neoplasia (adenoma/serrated polyp {greater than or equal to} 1 cm/villous/high-grade dysplasia), non-advanced neoplasia or normal. Our t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, a previously published study of our population demonstrated no significant differences for quality measures such as withdrawal time or endoscopist adenoma detection rates between the 3 cohorts which are also used in the current paper. (28) In summary, we observed that in NHCR patients receiving screening tests in the course of routine practice, those with positive mt-sDNA tests were more likely to have serrated polyps detected on subsequent colonoscopy than those with preceding positive FIT tests. Our findings are consistent with prior evidence suggesting that mt-sDNA tests are more likely to identify patients with serrated polyps than FIT tests, and expand on prior work by providing evidence on the types of serrated polyps found in patients after both types of stool tests.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, a previously published study of our population demonstrated no significant differences for quality measures such as withdrawal time or endoscopist adenoma detection rates between the 3 cohorts which are also used in the current paper. (28) In summary, we observed that in NHCR patients receiving screening tests in the course of routine practice, those with positive mt-sDNA tests were more likely to have serrated polyps detected on subsequent colonoscopy than those with preceding positive FIT tests. Our findings are consistent with prior evidence suggesting that mt-sDNA tests are more likely to identify patients with serrated polyps than FIT tests, and expand on prior work by providing evidence on the types of serrated polyps found in patients after both types of stool tests.…”
Section: Discussionmentioning
confidence: 60%
“…One additional concern is that there may have been differences with respect to endoscopic evaluation of patients with positive stool tests. However, a previously published study of our population demonstrated no significant differences for quality measures such as withdrawal time or endoscopist adenoma detection rates between the three cohorts which are also used in this article ( 27 ).…”
Section: Discussionmentioning
confidence: 68%
“…Our study reports significantly higher rates of SSP and ASP detection rates after positive FIT-DNA as compared to positive FIT testing. Prior observations demonstrate that FIT-DNA has a higher sensitivity for detecting conventional adenomas including advanced adenomas as compared to FIT [35,36,46]. These findings allow information to counsel patients on the utility of one versus the other test.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, we recruited 135 participants who all underwent histological or colonoscopy examination, the MT-sDNA test and tumor biomarker detection. We found that the risk score of MT-sDNA was significantly increased in CRC and adenoma patients compared with healthy controls which potentially makes it a promising non-invasive tumor biomarker for CRC detection[ 16 ].…”
Section: Discussionmentioning
confidence: 99%